Evolutionary life history theory as an organising framework for cohort studies: insights from the Cebu Longitudinal Health and Nutrition Survey. (17th February 2020) - Kuzawa, Christopher W.; Adair, Linda; Bechayda, Sonny A.; Borja, Judith Rafaelita B.; Carba, Delia B.; Duazo, Paulita L.; Eisenberg, Dan T. A.; Georgiev, Alexander V.; Gettler, Lee T.; Lee, Nanette R.; Quinn, Elizabeth A.; Rosenbaum, Stacy; et al.
ABSTRACT: By tracking a group of individuals through time, cohort studies provide fundamental insights into the developmental time course and causes of health and disease. Evolutionary life history theory seeks to explain patterns of growth, development, reproduction and senescence, and inspires a range of hypotheses that are testable using the longitudinal data from cohort studies. Here we review two decades of life history theory-motivated work conducted in collaboration with the Cebu Longitudinal Health and Nutrition Survey (CLHNS), a birth cohort study that enrolled more than 3000 pregnant women in the Philippines in 1983 and has since followed these women, their offspring and grandoffspring. This work has provided evidence that reproduction carries "costs" to cellular maintenance functions, potentially speeding senescence, and revealed an unusual form of genetic plasticity in which the length of telomeres inherited across generations is influenced by reproductive timing in paternal ancestors. Men in Cebu experience hormonal and behavioural changes in conjunction with changes in relationship and fatherhood status that are consistent with predictions based upon other species that practice bi-parental care. The theoretical expectation that early life cues of mortality or environmental unpredictability will motivate a "fast" life history strategy are confirmed for behavioural components of reproductive decision making, but not for maturational tempo, while our work points to a broader capacity for early life developmental calibration of systems like immunity, reproductive biology and metabolism. Our CLHNS findings illustrate the power of life history theory as an integrative, lifecourse framework to guide longitudinal studies of human populations.